Doctrinal, parliamentary, and juridical controversies over the Federal Control of the Press (1862-1890) (Quinto Sol, 2018)
This article analyses the instruments and limitations in the federal control of the press between the constitutional reform of 1860 and the end of the 1880s. To that end, we examine legislative debates, presidential addresses, Supreme Court rulings, articles of jurists in the specialized press and doctoral theses of the University of Buenos Aires that addressed this issue.
Keywords: freedom of the press; political press; federalism